2013
DOI: 10.1049/el.2012.4283
|View full text |Cite
|
Sign up to set email alerts
|

Towards in vivo biosensors for low‐cost protein sensing

Abstract: In vivo biosensing requires stable transistor operation in high‐salt concentration bodily fluids while exhibiting impermeability to mobile alkali ions that would otherwise render the metal‐oxide‐semiconductor (MOS) threshold voltage to drift. Metal oxide semiconductor capacitor structures using Al2O3 as the gate dielectric were soaked in a sterile physiological buffer solution (PBS) up to 24 hours and for thicknesses from 100 to 10 nm. The triangular voltage sweep technique characterised alkali ion penetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The current magnitude of the ISFET depends on the charge density (concentration) of the analyte molecules on the gate surface. Several studies have reported the Na + detection of graphene-and silicon-based ISFETs [4,5]. The objective of this work is to investigate the effect of the oxygen gas flow rate at room temperature sputtering of ITO thin film on the sensitivity to Na + .…”
mentioning
confidence: 99%
“…The current magnitude of the ISFET depends on the charge density (concentration) of the analyte molecules on the gate surface. Several studies have reported the Na + detection of graphene-and silicon-based ISFETs [4,5]. The objective of this work is to investigate the effect of the oxygen gas flow rate at room temperature sputtering of ITO thin film on the sensitivity to Na + .…”
mentioning
confidence: 99%
“…Ramesh et al have recently presented a new sensor fabrication technology where they replaced the silicon dioxide layer with a high quality dielectric made of Al 2 O 3 . 6 In this new configuration, the use of an Al 2 O 3 film instead of the thermally grown SiO 2 allowed them to eradicate the issue of mobile ion interference in the biosensors during protein concentration measurements. Al 2 O 3 was deposited on the surface of the silicon substrate using an atomic layer deposition process, with trimethyl aluminium and water as precursors.…”
Section: Reliable Biosensors For Low-cost Protein Sensingmentioning
confidence: 99%
“…Since nanosensors can interact directly with the most fundamental elements in matter, e.g., atoms and molecules, they can provide ultra-high sensitivity. One of the most promising applications of nanosensors is in vivo biosensing [4], [5], where nanosensors are injected into human body to collect real-time information. Nanosensors can be utilized both to detect well-known diseases at their very early stage as well as to provide new fundamental insights and understanding of biological processes that cannot be observed at the macroscopic level.…”
Section: Introductionmentioning
confidence: 99%